(untitled) (Global Journal of Human-Social Science, 2015)
Language proficiency tests for first, second or foreign language are designed for various purposes. Firstly, they may be part of the curriculum of a school or a university where students have to fulfill the requirement of the academic programme they have chosen. Secondly, they may also be a requisite in getting a particular type of job, and such like. In most of these tests, especially in the second type, the focus is on the candidate’s linguistic ability, whereas the social and cultural factors which form part of language usage isoften sidelined. This paper discusses the significance of these three factors -linguistics, social and cultural -in the formulation of language proficiency tests. An illustration is given in the proficiency tests for Malay for foreigners intending to study or work in Malaysia, consisting of three groups -the professionals, the students, and the workforce. The tests are designed against the backdrop of the socio-cultural milieu of Malaysia.Principles taken into consideration in the design of these tests are simplicity versus complexity, the choice of domains and register, authenticity, and sensitivity.